Diagnosis and clinical criteria for chronic endometritis - K G Serebrennikova; N A Arutyunyan; A I Alekhin (IP Berlin A.V., 2018)
Currently, the urgency of the problem of chronic endometritis is of medical and social importance, since it leads to impaired reproductive function. Among the risk factors there is a predominance of intrauterine devices and inflammatory complications after childbirth and abortion. Prolonged persistence of infectious agents in the endometrium in chronic endometritis leads to marked changes in the structure and function of the tissue, causes proliferative disorders, as well as disorders in cyclic transformation. Morphofunctional damage to the endometrium is not only the cause of infertility, unsuccessful attempts of in vitro fertilization (IVF) and embryo transfer (PE), miscarriage, and a decrease in the quality of life of women due to chronic pain, dyspareunia, uterine bleeding and discharge from the genital tract. Timely and accurate diagnosis is key to the success of the restoration of reproductive function. Treatment of chronic endometritis is a complex, phased process. One of the new methods is photodynamic therapy, which leads to the development of a photochemical reaction that destroys bacterial and tumor cells, and also has an antiviral effect.